First-trimester HbA1c in relation to plasma glucose concentrations in an oral glucose tolerance test at 12 to 16 weeks’ gestation—a population-based study - Mervi Jokelainen; Hannu Kautiainen; Arja Nenonen; Beata Stach-Lempinen; Miira M. Klemetti (Diabetology & Metabolic Syndrome, 2024)
Abstract Background Early-onset GDM often requires pharmacological treatment and is associated with adverse perinatal outcomes, but data is insufficient regarding the best methods to identify high-risk women requiring early GDM screening. The aim of this study was to analyze the diagnostic accuracy of HbA1c in the prediction of (1) plasma glucose concentrations > 90th percentile in an oral glucose tolerance test (OGTT) at 12–16 weeks’ gestation; and (2) pharmacologically treated early- or late-onset GDM. Methods HbA1c was measured at 8—14 weeks’ gestation in a population-based cohort of 1394 Finnish women recruited for the Early Diagnosis of Diabetes in Pregnancy (EDDIE) study between 3/2013 and 12/2016. Information on maternal risk factors were collected at recruitment. Subsequently, a 2-hour 75 g OGTT was performed at 12—16 weeks’ gestation (OGTT1), and if normal, repeated at 24–28 weeks’ gestation (OGTT2). Early- and late-onset GDM were diagnosed using the same nationally endorsed cut-offs for fasting, 1 h- and 2 h-plasma glucose: ≥5.3, ≥ 10.0mmol/l, and/or ≥ 8.6mmol/l, respectively. In total, 52/1394 (3.7%) women required metformin or insulin treatment for GDM, including 39 women with early-onset GDM diagnosed at OGTT1 and 13 women with late-onset GDM diagnosed at OGTT2. Results Maternal early-pregnancy HbA1c ≥ 35mmol/mol (≥ 5.4%) was the best cut-off to predict fasting or post-load plasma glucose > 90th percentile in OGTT1, but its diagnostic accuracy was low [AUC (95% CI) 0.65 (0.62 to 0.69), sensitivity 0.55 (0.49 to 0.60) and specificity 0.67 (0.64 to 0.70)] both alone and in combination with other maternal risk factors. However, HbA1c ≥ 35mmol/mol correlated positively with plasma glucose concentrations at all time points of OGTT1 and predicted pharmacologically treated GDM diagnosed at OGTT1 or OGTT2; AUC (95% CI) 0.75 (0.68 to 0.81), sensitivity 0.75 (0.61 to 0.86), specificity 0.64 (0.61 to 0.66). Conclusions In our population-based cohort, early-pregnancy HbA1c ≥ 35mmol/mol was positively associated with fasting and post-load plasma glucose concentrations in an OGTT at 12—16 weeks’ gestation and predicted pharmacologically-treated early- and late-onset GDM, suggesting potential utility in first-trimester identification of women at high risk of severe GDM subtypes.